Diversity of traditional vegetables and spices as local food security for the Gayo Tribe, Aceh, Indonesia - CUT NELLY; LIA FITRIYANA; TARAHA DILLA SANTI; SAUDAH SAUDAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nelly C, Fitriyana L, Santi TD, Saudah. 2024. Diversity of traditional vegetables and spices as local food security for the Gayo Tribe, Aceh, Indonesia. Biodiversitas 25: 4699-4711. Food is a fundamental necessity that is essential for human sustenance. The variety of traditional vegetables and spices, harvested from forests, fields, or home gardens, is critical to local food security. This study aimed to investigate the variety and utilization of local vegetables and spices by the Gayo community in Pining Sub-district, Gayo Lues District, Aceh, Indonesia and their contribution to sustainable food security. A field survey and semi-structured interviews five villages identified 75 taxa of vegetables and spices from 36 families with Zingiberaceae being the most dominant. The findings show women, who made up 68.0% of respondents, are key knowledge holders, passing down traditional plant knowledge through daily practices. Species such as Cocos nucifera L. and Etlingera elatior (Jack) R.M.Sm. showed the highest use value and frequency, underscoring their cultural and nutritional significance. However, the Gayo community faces threats, including land-use changes and the loss of traditional knowledge among the younger generation, jeopardizing plant conservation and sustainable food systems. Strategies such as sustainable agroforestry, local seed banks, and restoring traditional knowledge are essential to preserve biodiversity and ensure local food security. This research highlights the importance of preserving the diversity of traditional vegetables and spices as key elements of food security and cultural heritage.